RISE: Drone and precision agriculture technology for pineapple plantation / Dr Muhammad Asraf Hairuddin - Hairuddin, Muhammad Asraf (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
A research team, led by Dr Muhammad Asraf Hairuddin from the Faculty of Electrical Engineering at Universiti Teknologi MARA (UiTM) Kampus Pasir Gudang has developed an innovative solution to yield counting for pineapple fruits using drone technology.